Pelagia benovici sp. nov. (Cnidaria, Scyphozoa): a new jellyfish in the Mediterranean Sea - Piraino, Stefano; Aglieri, Giorgio; Martell, Luis; Mazzoldi, Carlotta; Melli, Valentina; Milisenda, Giacomo; Scorrano, Simonetta; Boero, Ferdinando (Zootaxa, 2014)
A bloom of an unknown semaestome jellyfish species was recorded in the North Adriatic Sea from September 2013 to early 2014. Morphological analysis of several specimens showed distinct differences from other known semaestome species in the Mediterranean Sea and unquestionably identified them as belonging to a new pelagiid species within genus Pelagia. The new species is morphologically distinct from P. noctiluca, currently the only recognized valid species in the genus, and from other doubtful Pelagia species recorded from other areas of the world. Molecular analyses of mitochondrial cytochrome c oxidase subunit I (COI) and nuclear 28S ribosomal DNA genes corroborate its specific distinction from P. noctiluca and other pelagiid taxa, supporting the monophyly of Pelagiidae. Thus, we describe Pelagia benovici sp. nov. Piraino, Aglieri, Scorrano & Boero.